Enhancing Cognitive Skills Through Interactive Digital Innovation in Computer Program Design For Vocational Students - Paranya Mingsamorn; Anek Putthidech; Salinun Boonmee (Journal of Applied Engineering and Technological Science (JAETS), 2026)
The objectives of this study were: 1) engaging developing digital innovative interactive on computer programming design for cognitive skills enhancement among vocational certificate students of  the Office of Vocational Education Commission 2) effectiveness evaluation 3) compare the cognitive skills of the control group and the experimental group; 4) assess satisfaction among experimental group students; and 5) evaluate acceptance of the developed innovation. The sample comprised second-year Business Computer students from Suphanburi Vocational College, Thailand who were placed in control and experimental groups via purposive sampling techniques. Research instruments included: 1) interactive digital innovation; 2) innovation evaluation form; 3) cognitive skill measurement; 4) satisfaction survey questionnaire; and 5) innovation acceptance form. Analyzed using means, standard deviation, and t-tests for both dependent and independent samples. The findings showed that the interactive digital innovation, based on Bloom’s Digital Taxonomy and integrated with tools like ClassPoint and WordWall, achieved the highest ratings for effectiveness (x̄ = 4.52), student satisfaction (x̄ = 4.53), and expert acceptance (x̄ = 4.51). The experimental group significantly improved their cognitive skills (p < 0.01). This innovation is effective for enhancing vocational students’ skills and serves as a model for 21st-century learning.